2003
DOI: 10.1046/j.1365-2915.2003.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal surveillance of the tick Ixodes ricinusfor borreliae

Abstract: Abstract. Host-seeking Ixodes ricinus (L.) (Acari: Ixodidae) were monitored for borreliae (Borrelia burgdorferi s.l.) using dark-field microscopy in South Moravia (Czech Republic) each May from 1991 to 2001 (150 nymphs, 100 females and 100 males each year). This survey revealed a mean annual percentage of infected ticks of 16.8% (range, 11.7±24.2) in nymphs, 24.9% (range, 16.5±33.6) in females and 26.1% (range, 17.1±37.3) in males. Annual incidence of Lyme borreliosis in humans of the area in the same period (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 18 publications
3
32
1
Order By: Relevance
“…The average positivity of ticks corresponds with other results from that region and ranges from 20-30%, depending on specific study and locality [14,16]. There are at least two studies in Central Europe testing for the presence of Bbsl in I. ricinus feeding on people.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The average positivity of ticks corresponds with other results from that region and ranges from 20-30%, depending on specific study and locality [14,16]. There are at least two studies in Central Europe testing for the presence of Bbsl in I. ricinus feeding on people.…”
Section: Discussionsupporting
confidence: 74%
“…Hubálek et al [14] reported that 16.8 -20.4 % of ticks collected in the region were positive for Bbsl. The aim of the presented study was to analyze the presence of Bbsl by RealTime PCR method in all ticks delivered to our laboratory from South Moravia, and collected from human skin.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of 3.3% of B. burgdorferi sensu lato PCR-positive ticks is relatively low compared with other studies probably due to the ecological habitat from where the samples were collected. Reported prevalences of B. burgdorferi sensu lato in ticks vary from 1.3% in Switzerland [5] to 55% in areas of Finland [23] with an average between 10 and 20% [9,22,29,36]. Here, we investigated a tick population living on pastures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already shown different ranges of prevalence between adults and nymphs, for Borrelia burgdorferi [9,22], for Babesia sp. [26] and Bartonella sp.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to assess prevalence of A. phagocytophilum in nymphal I. ricinus ticks in an area of South Moravia (Czech Republic) where Lyme borreliosis is endemic (Hubálek et al 2003). Host-seeking nymphal I. ricinus were collected by flagging low vegetation during September 2003.…”
mentioning
confidence: 99%